2009
DOI: 10.1098/rspa.2009.0255
|View full text |Cite
|
Sign up to set email alerts
|

The finite-product method in the theory of waves and stability

Abstract: This paper presents a method of analysing the dispersion relation and field shape of any type of wave field for which the dispersion relation is transcendental. The method involves replacing each transcendental term in the dispersion relation by a finite-product polynomial. The finite products chosen must be consistent with the low-frequency, lowwavenumber limit; but the method is nevertheless accurate up to high frequencies and high wavenumbers. Full details of the method are presented for a non-trivial examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…In the notation of §2a, this is E s /E = 100, ρ s /ρ = 10 and h s /h = 1 10 ; we also take equal Poisson's ratios ν s = ν = 0.3. The real and imaginary branches of the finite-product approximations (m s , n s , m, n) = (0, 0, 0, 1), (0, 1, 1, 2), (1, 2, 3, 4) and (3,4,7,8) for real frequency are plotted as dotted lines in figure 2a-h. The exact dispersion relation is superposed as solid lines, for detailed comparison of finite-product approximations with the exact results of §3.…”
Section: (D) Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the notation of §2a, this is E s /E = 100, ρ s /ρ = 10 and h s /h = 1 10 ; we also take equal Poisson's ratios ν s = ν = 0.3. The real and imaginary branches of the finite-product approximations (m s , n s , m, n) = (0, 0, 0, 1), (0, 1, 1, 2), (1, 2, 3, 4) and (3,4,7,8) for real frequency are plotted as dotted lines in figure 2a-h. The exact dispersion relation is superposed as solid lines, for detailed comparison of finite-product approximations with the exact results of §3.…”
Section: (D) Numerical Resultsmentioning
confidence: 99%
“…It follows from Chapman & Sorokin [7] that this is best achieved by taking n s = m s + 1 and n = m + 1, although the choices n s = m s and n = m are also good. This gives a two-parameter family of approximations (m s , m s + 1, m, m + 1).…”
Section: (C) the Main Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary justification of whether an overlap exists between the short-wave WKB method applied to long-wave beam models is now given. In Chapman & Sorokin [14], it is demonstrated that the beam model formulation for uniform beams effectively corresponds to neglecting O(h 2 /λ 2 ) terms, where h is the local cross-wise dimension and λ is the wavelength. Denoting μ = h/λ and by introducing the relation μ = q , it can be shown that for 1/2 < q < 1 both the longwave beam assumption, μ 1, and short-wave WKB assumption, λ/l 1, are fulfilled when 1.…”
Section: Models Of Non-uniform Beamsmentioning
confidence: 99%
“…The inspiration for this work arose from reading the article (Chapman (2010)) in which the authors found that by replacing trigonometric functions by a f nite product polynomial and a Gamma function expression they were able to get very good approximations for the roots of eigenvalue equations. The replacement was exact and followed from the well known identities between the Gamma function and trigonometric functions.…”
Section: Introductionmentioning
confidence: 99%